2007
DOI: 10.1104/pp.107.112995
|View full text |Cite
|
Sign up to set email alerts
|

Specificity of RCN1-Mediated Protein Phosphatase 2A Regulation in Meristem Organization and Stress Response in Roots

Abstract: Protein dephosphorylation by the serine/threonine protein phosphatase 2A (PP2A) modulates a broad array of cellular functions. PP2A normally acts as a heterotrimeric holoenzyme complex comprising a catalytic subunit bound by regulatory A and B subunits. Characterization of the regulatory A subunit isoforms (ROOTS CURL IN NAPHTHYLPHTHALAMIC ACID1 [RCN1], PP2AA2, and PP2AA3) of Arabidopsis thaliana PP2A has shown that RCN1 plays a primary role in controlling root and hypocotyl PP2A activity in seedlings. Here we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
91
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(96 citation statements)
references
References 65 publications
5
91
0
Order By: Relevance
“…Homology searches identified four Arabidopsis SAPS domain-like proteins (SAL1-4), which share 45 to 72% sequence similarity. The Arabidopsis Information Resource public database shows that SAL proteins are located in either the plasma membrane or the endomembrane system (http:// www.Arabidopsis.org/), which is similar to the subcellular localization of PP2AAs (Michniewicz et al, 2007;Blakeslee et al, 2008) and the membrane localization of FyPPs (see Supplemental Figure 9 online). We examined protein-protein interactions between these subunits in yeast and plants.…”
Section: Fypp1 and Fypp3 Directly Dephosphorylate Pin Proteinsmentioning
confidence: 52%
See 2 more Smart Citations
“…Homology searches identified four Arabidopsis SAPS domain-like proteins (SAL1-4), which share 45 to 72% sequence similarity. The Arabidopsis Information Resource public database shows that SAL proteins are located in either the plasma membrane or the endomembrane system (http:// www.Arabidopsis.org/), which is similar to the subcellular localization of PP2AAs (Michniewicz et al, 2007;Blakeslee et al, 2008) and the membrane localization of FyPPs (see Supplemental Figure 9 online). We examined protein-protein interactions between these subunits in yeast and plants.…”
Section: Fypp1 and Fypp3 Directly Dephosphorylate Pin Proteinsmentioning
confidence: 52%
“…To further test the genetic interactions between FyPPs and RCN1 and SAL1, we introduced the f1 f3 mutation into the rcn1-6 (Blakeslee et al, 2008) and sal1 mutant backgrounds. Both rcn1 f1 f3 and sal1 f1 f3 triple mutants had shorter roots than their parental lines ( Figure 8A).…”
Section: Pp6 Acts Antagonistically With Pid To Regulate Plant Developmentioning
confidence: 99%
See 1 more Smart Citation
“…Although it has been previously shown that PP2AA1 is localized cytosolically but cofractionates to an appreciable extent with plasma membrane proteins (Michniewicz et al, 2007;Blakeslee et al, 2008), to our knowledge, the effect of brefeldin on this localization has not yet been reported. PP2AA1-GFP permeated the cytoplasm; however, following 2-d treatment with as low as 3 mM brefeldin, appreciable PP2AA1-GFP moved into large central bodies (Figure 9) identified as nuclei by staining with a DNA-specific dye (see Supplemental Figure 5 online).…”
Section: Loss Of Pp2aa1 Enhances Responses To Brefeldinmentioning
confidence: 71%
“…In a recent study (Blakeslee et al, 2008), Arabidopsis rcn1-1 seedlings showed increased auxin transport but decreased root gravitropism. A sizeable fraction of RCN1 protein was localized in a microsomal membrane fraction in roots, and plants expressing YFP-RCN1 showed some enrichment adjacent to the plasma membrane as do both phot1 ) and phot2 (Kong et al, 2007).…”
Section: Discussionmentioning
confidence: 99%